Research on Von Bertalanffy model and its application for predicting recoverable reserves and production of oilfield. Issue 4 (March 2021) - Liu, Feng; Zhou, Ahuan; Yu, Linjun; Wang, Yue; Yang, Fei
Abstract: Water drive type curves are simple, convenient and practical in reservoir engineering, which is widely used in reservoir production performance analysis. However, the commonly used water drive type curve can only draw one curve between water cut and recoverable reserves recovery degree, which greatly limits the application range of water drive curve. At the same time, the fitting of straight line section of water drive type curve is often affected by artificial selection, and the error is large. In order to better describe and reflect the rising law of water cut in different type reservoirs, the new water drive type curve is established, and the relationships between water cut and cumulative production, water cut and recovery degree of recoverable reserves are derived. Through MATLAB software programming and multi parameter fitting method, the parameters in the new water drive type curve can be easily calculated. The f w - R * curve shape of the new model includes convex curve, concave curve and S -shape curve. The new water drive type curve is applied to two actual reservoirs. The new curve fits well with the low water cut stage of the Baolang oilfield, and the error is small, which can be used to predict the future production performance of the oilfield. At the same time, the new water drive type curve is consistent with the change trend of the whole production stage of the Saertu oilfield, and the error is small, too. which can be used for the prediction of the whole production period and high water cut stage of the reservoir. The new model expands the application range of water drive type curve and provides reference for production performance prediction of other similar oilfields.